Hubungan Antara Kematangan Beragama Dengan Kompetensi Interpersonal Mahasiswa - Fuad Nashori; Sugiyanto (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2000)
This research aimed to examine the relationship between the mature religious sentiment and the interpersonal competence. The hypothesis was tested there was a positive correlation between mature religious sentiment and the interpersonal competence.The subject of the research were psychology student in Yogyakarta (100 students from Islamic University of Indonesia, 101 students from Gadjah Mada University). Two instruments were administered to gather the data: the interpersonal competence scale and the mature religious sentiment scale.  The product Moment Correlation technique was applied to analyze the data. The result indicated that there was a positive and significant correlation between mature religious sentiment and the interpersonal competence.  Key Words    :   the interpersonal competence, the mature religious sentiment